Insurance Company’s Undertaking Model Based on ARIMA Algorithm - Wang, Kaiyue; Xu, Changcong (Transactions on Computer Science and Intelligent Systems Research, 2024)
Extreme weather can cause economic losses to residents which can be reduced by purchasing insurance. From the perspective of insurance company, to earn maximum profit, they need to carefully consider whether to provide insurance services in a region, especially for where natural disasters happen frequently. The paper puts forward Natural disaster prediction model and Insurance company undertaking model. In the first part, the paper uses ARIMA algorithm to forecast when will the natural disasters happen, including extreme high and low temperature, droughts and floods, and tornadoes. Data form four different regions follow as example. In the second part, the paper applies C-L risk model, and converts it into Compensation forecast model. As an example, this model is also used to value the insurance details in Tempa, America and Jakarta, Indonesia. When the total insured value of the two places is greater than 44 billion dollars and 143 billion dollars respectively, the insurance company can make a profit.